The Effect Of Cooperative Integrated Reading And Composition (CIRC) Model On Students’ Reading Comprehension - Cindy Nadila; Iskandar Zulkarnain; Linda Astuti Rangkuti (Journal of Innovative and Creativity, 2025)
The objective of this research is to investigate if Cooperative Integrated Reading and Composition (CIRC) Model affects students’ reading comprehension. This research was conducted by using experimental research design. The population of this study was the tenth grade of MAS Al-Washliyah Pantai Cermin which has two parallel classes namely X-A and XB. Each class consisted of 19 and 20 students. So, the total number of population was 39 students. Cluster random sampling with Spin the Wheel Technique was employed in selecting the sample. The class X-A was selected as experimental group and the class X-B was selected as control group. The experimental group was taught by applying Cooperative Integrated Reading and Composition (CIRC) Model while the control group was taught with Convensional. The instrument used in this research was reading test. The data were analyzed by using t-test. After the data were calculated, it was found that tobserved was higher than ttable (0.001>0.05) with the degree of freedom df =37 at the level of significance α =0.05. It meant that H0 was accepted and H1 was successfully rejected. Thus, applying Cooperative Integrated Reading and Composition (CIRC) Model significantly affects students’ achievement in reading descriptive text.